Inducers of Autophagy and Cell Death: Focus on Copper Metabolism - Weikang Ling; Shuo Li; Yang Zhu; Xin Wang; Dongmei Jiang; Bo Kang (Ecotoxicology and Environmental Safety)
Copper is an essential trace element in biological systems, playing a key role in various physiological functions, including redox reactions and energy metabolism. However, an imbalance in copper homeostasis can induce oxidative stress, mitochondrial dysfunction, and inhibition of the ubiquitin-proteasome system, ultimately leading to significant cytotoxicity and cell death. According to recent research, copper can bind to lipoylation sites on proteins involved in the tricarboxylic acid cycle, causing aggregation of lipoylated proteins, the loss of Fe-S cluster proteins, proteotoxic stress, and ultimately, cell death. This new type of programmed cell death is called “Cuproptosis”. Furthermore, autophagy may be activated by a disruption in copper homeostasis, while it plays a dual role in regulating copper-induced cell death by acting both as an inhibitor of cell death and as a promoter of cytotoxicity. This review summarizes research progress on copper metabolic patterns, molecular mechanisms of copper-induced cell death, and mechanisms of copper-induced autophagy-cytotoxicity interactions. Meanwhile, the application of copper-induced cell death in cancer therapy is discussed, aiming to provide new insights and guiding future research toward advancing cancer therapy.